(3eaGJjM GdZjHs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3ShQI GdCMbGa (B(((3Me JfRjd GdcJGH ef Gddg GdYRjR GdMcje (B))q s
(3BNQgG (B:s
(3jJdhg GdLRA GdPi HYOg ShQI GdaJM Ef TGA Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3Ydi dhMI GdYfhGf Jedcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B558s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1756s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs